2019
DOI: 10.29333/ejecs/147
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical studies focused on gender discrimination against Roma women in the Czech Republic

Abstract: Discrimination affects the lives of many Roma women in different areas of their lives. Issues such as unequal access to the labor market for women and men, domestic violence, stereotypical expectations of the roles of women in society, other expectations in education for women and men are deepening in the context of discrimination and ethnicity expectations. Roma women in the Czech Republic are among the groups most at risk of unemployment. However, repeated failures to find a job reduce their self-esteem and,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Thus the prevalent rigid cultural values and normative practices are used against infertile women in Pakistani society that prone women to many violence including physical and non-physical (Zarar et al, 2017). However, the empirical work of Merhaut (2019) reported that women in Roma experience prejudicial treatment in all walks of life that negatively affected their quality of life. Taking together, study findings and prior work it could be affirmed that cultural values and practices not only affected women's lives in Pakistan but also in other parts of the world too.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the prevalent rigid cultural values and normative practices are used against infertile women in Pakistani society that prone women to many violence including physical and non-physical (Zarar et al, 2017). However, the empirical work of Merhaut (2019) reported that women in Roma experience prejudicial treatment in all walks of life that negatively affected their quality of life. Taking together, study findings and prior work it could be affirmed that cultural values and practices not only affected women's lives in Pakistan but also in other parts of the world too.…”
Section: Discussionmentioning
confidence: 99%
“…National minorities are disproportionally reliant on the private sector for employment. Moreover, issues related to intersectionality are also present, with minority women (Merhaut 2019) often facing discrimination on two demographic fronts (Cârstoces & Willis 2021).…”
Section: Slovenes In Croatiamentioning
confidence: 99%
“…According to Michálek and Veselovská (2016), education has the lowest value in the Roma community. Merhaut (2019) states that Roma families set lower expectations for girls' education, which is influenced by established Roma traditions, i.e., a woman is not intended tohave a job and providing financial support for the family, but her role is to raise children and take care of the household. Educational practice, as well as many research findings (Hlebová, 2018;Ľuptáková, 2008;Rosinský, 2006) point to a low self-understanding of the school success of Roma pupils.…”
Section: Introductionmentioning
confidence: 99%